A computational framework for modelling impact induced damage in ceramic and ceramic-metal composite structures. (15th March 2017) - Chakraborty, Sukanta; Islam, Md Rushdie Ibne; Shaw, Amit; Ramachandra, L.S.; Reid, S.R.
Abstract: When ceramic or ceramic-metal composite structures are subjected to impact loading, they undergo various deformation phases such as plastic yielding, pulverization, fragmentation, tensile spalling, interface debonding, penetration etc. In order to study these phenomenological characteristics and produce insightful observation, numerical simulation is inevitable. Apart from reasonably accurate constitutive model, a numerical scheme must also accommodate any possible loss (in the case of fragmentation and material separation) of the continuum nature of the problem domain. This is generally difficult to achieve through mesh-based methods. In this study a computational framework based on smoothed particle hydrodynamics (SPH), a particle-based method, is explored and revamped. Damage growth and localized cracks are modelled through a pseudo-spring analogy, wherein particle-interactions are modulated based on material strength reduction after damage initiation. Different material models are coupled in this analogy for investigating different paradigms of penetration mechanics in ceramic and ceramic-metal composites. The computational framework is first validated through experimentally obtained results of flyer plate tests on Silicon Carbide (SiC) disc. Subsequently the framework is explored in simulating more complex failure mechanisms involving multiaxial crack interaction and fragmentation in ceramic-metal composite target system.